Economic Evaluations of Interventions for Snakebites : A Systematic Review (2020)
ABSTRACT : Background: Snakebite is an often-neglected event with a high rate of mortality and is concentrated in poor areas. We aimed to assess the economic impact and health effects of the implementation of interventions for snakebites through a systematic review of the scientific literature. Methods: Thirty search strategies were conducted in seven databases, applying PRISMA’s identification, screening, selection, and inclusion phases. The reproducibility of the selection of studies and the extraction of information were guaranteed. The methodological quality was evaluated using the Consolidated Health Economic Evaluation Reporting Standards. Qualitative synthesis and meta-analysis were performed for determining the average costeffectiveness (ACE) for each death and disability-adjusted life years (DALY) avoided. Results: Six cost-effectiveness studies were included for the supply of antivenom (AV), taken as outcomes on days of hospitalization or in ICU, death and DALYs avoided. All studies only included institutional costs, and majority of them did not specify the analytical model or economic evaluation parameters and did not perform uncertainty analyses. The management protocol standardization with interdisciplinary attention improves ACE of AV. Cost-effectiveness ratio (CER) of treatment with AV was USD 1253 (constant value for the year 2017, adjusted by purchasing power parity) for each death avoided and USD 51 per DALY avoided. Conclusion: High cost-effectiveness of the AV treatment for snakebites was evidenced, which shows that the allocation of resources for this event should be a healthcare priority in addition to implementation of strategies that improve the access to, opportunity, and quality of hospital and pre-hospital care and reduce the cost of AV.